Is nasal MRSA carriage a concern among African people and local communities in North Cyprus? - Arikan, Ayse; Nassar, Noor; Awosanya, John O; Güvenir, Meryem; Ünaldi, Özlem; Bakkaloğlu, Zekiye; Süzük Yildiz, Serap (The Journal of Infection in Developing Countries, 2026)
Introduction: The long-standing epidemic of antimicrobial resistance (AMR) has proven to be a challenging problem to solve and is becoming even more complex in a globalized world where there is little evidence of AMR patterns among multinational communities. This study aimed to determine the frequency of methicillin resistant Staphylococcus aureus (MRSA) carriage among African and local students in Northern Cyprus. Methodology: Nasal swabs were collected from African and local students between October 2023 and December 2023. The clinical samples were screened for the presence of MRSA. AMR bacterial isolates were tested by phenotypic and genotypic analysis to determine the MRSA status. Results: A total of 300 participants were included in the study: One hundred and fifty of them were African students (50%) and 150 were local students (50%), The prevalence of nasal MRSA carriage in African and local students was determined as 3% and 6%, respectively. Conclusions: This study is a population-based study investigating the prevalence and distribution of MRSA in Africa and is the first to be conducted in the local population of Northern Cyprus. It highlights the presence of MRSA in the community and the impact of global migration on AMR, highlighting the need for public health measures.